Immediate and simultaneous sensory reorganization at cortical and subcortical levels of the somatosensory system - Faggin, Barbara M. (The National Academy of Sciences of the USA, 1997)
The occurrence of cortical plasticity during adulthood has been demonstrated using many experimental paradigms. Whether this phenomenon is generated exclusively by changes in intrinsic cortical circuitry, or whether it involves concomitant cortical and subcortical reorganization, remains controversial. Here, we addressed this issue by simultaneously recording the extracellular activity of up to 135 neurons in the primary somatosensory cortex, ventral posterior medial nucleus of the thalamus, and trigeminal brainstem complex of adult rats, before and after a reversible sensory deactivation was produced by subcutaneous injections of lidocaine. Following the onset of the deactivation, immediate and simultaneous sensory reorganization was observed at all levels of the somatosensory system. No statistical difference was observed when the overall spatial extent of the cortical (9.1 ± 1.2 whiskers, mean ± SE) and the thalamic (6.1 ± 1.6 whiskers) reorganization was compared. Likewise, no significant difference was found in the percentage of cortical (71.1 ± 5.2%) and thalamic (66.4 ± 10.7%) neurons exhibiting unmasked sensory responses. Although unmasked cortical responses occurred at significantly higher latencies (19.6 ± 0.3 ms, mean ± SE) than thalamic responses (13.1 ± 0.6 ms), variations in neuronal latency induced by the sensory deafferentation occurred as often in the thalamus as in the cortex. These data clearly demonstrate that peripheral sensory deafferentation triggers a system-wide reorganization, and strongly suggest that the spatiotemporal attributes of cortical plasticity are paralleled by subcortical reorganization.